Tea Polyphenols Prevent Sepsis-Induced Lung Injury via Promoting Translocation of DJ-1 to Mitochondria - Jia, Chun-Mei; Zhang, Feng-Wei; Wang, Shu-Juan; Wang, Wei; Li, Yong (Frontiers in Cell and Developmental Biology, 2021)
Background: Sepsis is the systemic inflammatory response syndrome caused by infection, which commonly targets on the lung. Tea polyphenols (TP) have many pharmacological activities, but their role in sepsis induced lung injury remains unclear. Results: Injection of TP after cecal ligation and puncture (CLP) operation elevated the survival rate in a concentration dependent manner. TP treatment improved alveoli structure injury under CLP operation. CLP surgery increased the expression of inflammatory factors IL1β, IL6 and TNFα expression, which was reversed by TP injection. In addition, CLP operation promoted apoptosis and senescence in tissues and cells during lung injury, while TP administration removed the damaged role of CLP on lung tissues and cells. Furthermore, CLP operation or LPS (lipopolysaccharide) treatment induced dysfunction of mitochondria in lung tissues and cells, but TP contributed to recover mitochondria function, which exhibited as inhibition of ROS production inhibition and increase of ATP content and Mitochondrial membrane potential (MMP). Interestingly, DJ-1 was inhibited by CLP operation but promoted by TP treatment. Overexpression of DJ-1 reversed the injury of LPS on L2 cells and recovered mitochondria normal function. And silencing of DJ-1 in rats or alveolar epithelial cells blocked the protection effect of TP. Conclusion: Our research revealed that TP protected against lung injury via upregulating of DJ-1 to improve mitochondria function, which contributed to the prevention and treatment of sepsis induced lung injury.